Intra-V1 functional networks and classification of observed stimuli - Ontivero-Ortega, Marlis; Iglesias-Fuster, Jorge; Perez-Hidalgo, Jhoanna; Marinazzo, Daniele; Valdes-Sosa, Mitchell; Valdes-Sosa, Pedro (Frontiers in Neuroinformatics, 2024)
Introduction: Previous studies suggest that co-fluctuations in neural activity within V1(measured with fMRI) carry information about observed stimuli, potentially reflecting various cognitive mechanisms. This study explores the neural sources shaping this information by using different fMRI preprocessing methods. The common response to stimuli shared by all individuals can be emphasized by using inter-subject correlations or de-Discussion: Our findings indicate that both inter-subject common responses and participantspecific activity contribute to the information in intra-V1 co-fluctuations, albeit through distinct sub-networks. Deconvolution, that enhances subject-specific activity, highlighted interhemispheric links for Global stimuli. Further exploration of intra-V1 networks promises insights into the neural basis of attention and perceptual organization.